PEMBERIAN SALEP EKSTRAK DAUN PISANG AMBON (Musa paradisiaca var.sapientum) TERHADAP ULKUS TIKUS DIABETIK YANG DIINDUKSI ALOKSAN: Array - La Ode Muhammad Anwar; Armi Armi; Marselina Marselina; Masita Sari Dewi; Salma Hilmy Rusydi Hashim; Embriana Dinar Pramestyani; Nuzul Gyanata Adiwisastra; Cyto Yudha Kurniawan; Cindy Junita Romli; Awanda Pramudita Okhanza; Mahesa Mahesa (Midwinerslion : Jurnal Kesehatan STIKes Buleleng, 2024)
Introduction: Diabetes is a chronic condition that occurs when the pancreas does not produce enough insulin or when the body cannot adequately use the insulin it does produce. This increases the sugar in the blood. One of the effects of diabetes is the formation of ulcers. Method: The ointment preparation formulations that have been made are then evaluated, including organoleptics, homogeneity, spreadability, pH, viscosity, and stability. The test animals used were 30 test animals consisting of 5 groups, each group consisting of 5 rats. Group I rats were given a topical preparation of 10% extract ointment. Group II was given a topical preparation of ointment extract with a concentration of 15%. Group III topical preparation of ointment extract with a concentration of 20% Group IV without treatment. Group V, as a positive control, was given betadine ointment. Induction of rats was done by giving alloxan monohydrate intraperitoneally. Results: Ulcer testing on 10% ointment has the best healing rate compared to the control. The 20% ointment took four days to heal the ulcer. The 15% ointment and the control took six days to heal. Conclusion: The 10% ointment formula has the best healing of diabetic ulcers compared to the control given.